2007
DOI: 10.1111/j.1365-2524.2007.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Network-based rehabilitation increases formal support of frail elderly home-dwelling persons in Finland: randomised controlled trial

Abstract: The AGE study is a national randomised, long-term, multicentre research project aimed at comparing a new network-based rehabilitation programme with the use of standard health and social services. The use of home help services is associated with increasing age, living alone and having difficulties with activities of daily living. During a rehabilitation intervention the elderly participants' need for care can be assessed. The focus of this paper is to investigate the possible effects of the network-based rehab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Four studies covered chronic care: one of good quality, targeted people at high risk of ‘institutionalisation’ (Ollonqvist et al. 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies covered chronic care: one of good quality, targeted people at high risk of ‘institutionalisation’ (Ollonqvist et al. 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The South Australian Health Plus trial targeting diverse patient groups reported improved physical function in the intervention group over time (Battersby 2005, Battersby et al. 2007), whereas a network rehabilitation model showed no effect on function but improved subjective health (Ollonqvist et al. 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The meetings focused on health promotion and control. One intervention (Ollonqvist et al 2008) contains three inpatient rehab periods with individual and group sessions plus home activation days and home visits for personal hygiene and assistive devices. Liang et al (1986) used a stepped-up treatment (on top of nursing and social services) provided by a physician and physical therapist focusing on assistive devices and home modification and supervised exercises.…”
Section: Other Interventions (N = 6)mentioning
confidence: 99%
“…In its multidimensional aspect, this support can be classified according to its characteristics: direction (received or offered); disposition (availability or execution); way of measurement (described or evaluated); content (emotional, instrumental, informative, evaluative); social network (family, friends, neighbors, work colleagues, the community, and other) (10) . Besides that, two different social support modalities still need to be considered: the formal support (support system offered/provided by the State and institutions), that has an infrastructure with the specific purpose of support in certain areas and which utilize professionals or volunteers to reach their goals; and the informal support (offered/provided by the family, neighbors, friends, and community), motivated by feelings of affection or obligation (13)(14) . According to the Human Development Report of 1999 (15) , the social support acts as a fundamental role in the formation of human capabilities and in human development.…”
Section: Introductionmentioning
confidence: 99%